Poor treatment outcomes of acute exacerbations of chronic obstructive pulmonary disease and their associated factors among admitted patients in East Gojjam, 2023 - Getnet, Melaku Tadele; Afenigus, Abebe Dilie; Gete, Menberu; Emrie, Ambaw Abebaw; Tsegaye, Dejen (Frontiers in Medicine, 2024)
Background Acute exacerbation of chronic obstructive pulmonary disease (COPD) poses a significant public health challenge globally, resulting in considerable health and economic burden. To date, there has been insufficient research in Ethiopia regarding poor treatment outcomes associated with these acute exacerbations. Objective This study aims to assess the poor treatment outcomes of acute exacerbations of chronic obstructive pulmonary disease and identify the associated factors among admitted patients in East Gojjam in 2023. Design An institutional-based cross-sectional study design was employed. Methods The institutional-based cross-sectional study was conducted from 7 April 2023 to 7 May 2023, involving 384 participants selected through simple random sampling. Data were extracted from patient charts and registers. Data entry was performed using EpiData, and the analysis was conducted using IBM SPSS Statistics version 26 software. Binary logistic regression analysis was used to identify the association between dependent and independent variables. Variables with a p-value of <0.25 in the bivariable logistic regression analysis were considered candidates for multivariable logistic regression. Variables with a p-value of <0.05 were considered statistically significant. Results Out of a total of 346 patients, 99 (28.6%) (95% CI, 23.9–33.3) developed poor treatment outcomes following exacerbations of chronic obstructive pulmonary diseases. Poor treatment outcomes were significantly associated with the following variables: age 65 or older (AOR = 3.9; 95% CI: 1.57–9.71), presence of comorbidities (AOR = 2.6; 95% CI: 1.287–5.20), a hospital stay longer than 7 days (AOR = 3.9; 95% CI: 1.97–7.70), and low oxygen saturation (<88%) (AOR = 9.0; 95% CI: 4.43–18.34). Conclusion Approximately one-third of the patients treated for acute exacerbations of chronic obstructive pulmonary disease at the Debre Markos Comprehensive Specialized Hospital experienced poor treatment outcomes. There is a significant association between poor treatment outcomes of acute exacerbation of chronic obstructive pulmonary disease and age ≥ 65 years, having comorbidities, prolonged hospital stay, and low oxygen saturation.